Measuring Online Wellbeing: A Scoping Review of Subjective Wellbeing Measures - Ong, Zhen Xin; Dowthwaite, Liz; Perez Vallejos, Elvira; Rawsthorne, Mat; Long, Yunfei (Frontiers in Psychology, 2021)
With the increasing importance of the internet to our everyday lives, questions are rightly being asked about how its’ use affects our wellbeing. It is important to be able to effectively measure the effects of the online context as it allows us to assess the impact of specific online contexts on wellbeing that may not apply to offline wellbeing. This paper describes a scoping review of English language, peer-reviewed articles published in MEDLINE, EMBASE, and PsychInfo between 1st January 2015 and 31st December 2019 to identify what measures are used to assess subjective wellbeing, and in particular to identify any measures used in the online context. 240 studies were identified; 160 studies were removed by abstract screening and 17 studies were removed by full-text screening, leaving 63 included studies. 56 subjective wellbeing scales were identified with 18 excluded and 38 included for further analysis. Only 1 study was identified researching online wellbeing and no specific online wellbeing scale was found. Therefore, common features of the existing scales, such as the number and type of questions are compared to offer recommendations for building an online wellbeing scale. Such a scale is recommended to be between 3 and 20 questions, using mainly 5 point Likert or Likert-like scales to measure at least positive and negative affect, and ideally life satisfaction, and to use mainly subjective evaluation. Further research is needed to establish how these findings for the offline world effectively translate into an online measure of wellbeing.